Effectiveness of an Intervention Program on Nurses’ Performance toward Neonatal Endotracheal Suctioning Procedure - Qasem, Alaa (Iraqi National Journal of Nursing Specialties, 2022)
Objective(s): To evaluate nurses’ Practice toward neonatal endotracheal suctioning procedure, and to determine the effectiveness of the interventional program on nurses’ practices, as well as to find out the relationship between nurses’ practice and their demographic characteristics.Methodology: A Pre-experimental, one group design, was carried out to achieve the objectives of the current study using the evaluation approach and the implementation of the education program for the period from January 17 to June 31, 2022. A non- probability, purposive sample of (24) nurses were selected from the Neonatal Intensive Care Unit at Pediatric Teaching Hospital/ Medical City Department. A checklist was developed consists of two parts: part I: Nurses’ demographic characteristics, and part II: Evaluation of nurses' Practice toward neonatal endotracheal suctioning procedure which consist of three domains (60) item, using the observation technique for data collection….Results: The results of the data showed that all of the (24) neonatal intensive care unit nurses had an Inadequate level of Practice in the pre-test, while the results of the post-test after implementing the program was adequate through apply all steps the suctioning procedure.Conclusions: The intervention program, after its application, had a positive and effective effect on the practices of neonate intensive care unit nurses. While there was a clear change for the better in their practices after apply the program. Recommendations: The researcher recommends the implementation and generalization of the interventional program for nurses' practices and its inclusion in the nursing curriculum. It also recommends that the Ministry of Health appoint and distribute university degree holders only in all neonatal intensive care units and compulsory nurses to participate in training courses intensively and continuously.